A Comparative Study of Linguistic Features in Gender Communication in Moroccan televised Political Panels - SADOUK , LAILA (Revue Internationale du Chercheur, 2022)
The purpose of this study is to determine whether Moroccan men and women communicate differently. The current study seeks to produce a report on face-to-face communication in MED1 TV’s broadcast political interviews. To determine the variations in the usage of linguistic elements such as hedges, intensifiers, super polite forms between men and women, data was obtained by recording and transcribing excerpts from two interviews. According to the findings of the study, there are no differences between men and women in the use of linguistic characteristics in their communication. In addition, the results indicate that the usage of linguistic elements is influenced by other variables, such as the skill of the participants in a particular location and context of interaction. This research is limited to describing gender communication in a certain formal setting. The study suggests that language behavior related with gender stereotypes can be challenged if such behaviors are investigated in a variety of contexts.